Oil Shocks in a Global Perspective : Are they Really That Bad? - Rasmussen, Tobias (IMF Working Papers; Working Paper ;, 2011)
Using a comprehensive global dataset, we outline stylized facts characterizing relationships between crude oil prices and macroeconomic developments across the world. Approaching the data from several angles, we find that the impact of higher oil prices on oil-importing economies is generally small: a 25 percent increase in oil prices typically causes GDP to fall by about half of one percent or less. While cross-country differences in impact are found to depend mainly on the relative size of oil imports, we also show that oil price shocks are not always costly for oil-importing countries: although higher oil prices increase the import bill, there are partly offsetting increases in external receipts. We provide a small open economy model illustrating the main transmission channels of oil shocks, and show how the recycling of petrodollars may mitigate the impact.